Construction of Fluorine‐ and Piperazine‐Engineered Covalent Triazine Frameworks Towards Enhanced Dual‐Ion Positive Electrode Performance. Issue 4 (8th September 2022) - Wang, Tao; Gaugler, James Anthony; Li, Meijia; Thapaliya, Bishnu Prasad; Fan, Juntian; Qiu, Liqi; Moitra, Debabrata; Kobayashi, Takeshi; Popovs, Ilja; Yang, Zhenzhen; Dai, Sheng
Abstract: Organic positive electrodes featuring lightweight and tunable energy storage modes by molecular structure engineering have promising application prospects in dual‐ion batteries. Herein, a series of highly porous covalent triazine frameworks (CTFs) were synthesized under ionothermal conditions using fluorinated aromatic nitrile monomers containing a piperazine ring. Fluorinated monomers can result in more defects in CTFs, leading to a higher surface area up to 2515 m 2 g −1 and a higher N content of 11.34 wt % compared to the products from the non‐fluorinated monomer. The high surface area and abundant redox sites of these CTFs afforded high specific capacities (up to 279 mAh g −1 at 0.1 A g −1 ), excellent rate performance (89 mAh g −1 at 5 A g −1 ), and durable cycling performance (92.3 % retention rate after 500 cycles at 2.0 A g −1 ) as dual‐ion positive electrodes. Abstract : CTFs for the win : Highly porous covalent triazine frameworks (CTFs) with high surface areas up to 2515 m 2 g −1 and abundant redox sites are synthesized under ionothermal conditions using fluorinated monomers containing a piperazine ring. These highly porous CTFs exhibit high specific capacity, impressive rate performance, and durable cycling performance as dual‐ion positive electrodes.